PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP PRESTASI KERJA KARYAWAN PT. BANK SAHABAT PURBA DANARTA KANTOR PUSAT SEMARANG - Krissabda, Audi Surya; Suryoko, Sri; Listyorini, Sari (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2013)
Work performance is a very desirable outcome, either by employees or the workers themselves and the company. Compensation and Motivation has been found to increase employee performance. Therefore, two things need to be considered by the company in order to improve work performance. PT. Bank Sahabat Purba Danarta Pusat Semarang is one of the banks engaged in microfinance and has a new policy is to recruit staff on a large scale, but have not been able to realize the given target. The purpose of this reseacrh are: (a) To find there is an effect of compensation to work performance at PT. Bank Sahabat Purba Danarta. (b) To find there is an effect of motivation to work performance at PT. Bank Sahabat Purba Danarta. (c) To find there is an effect of compensation and motivation to work performance at PT. Bank Sahabat Purba Danarta. This research type is explanatory research to the 39 respondents to the census approach. Data collection techniques in this study using interview techniques, by means of questionnaires and literature study. The data obtained were analyzed qualitatively and quantitatively using analytical tools such as cross tables, test validity, reliability testing, simple linear regression, multiple linear regression and hypothesis testing with the t test and F test. The conclusion of this study is that there is a positive effect between compensation and motivation of the employees' performance of PT Bank Sahabat Purba Danarta kantor Pusat Semarang. The higher compensation and motivation of the employees' work performance will increase, and vice versa. Suggestions for increasing employees' work performance for the company to increase its attention to compensation and motivation that will ultimately improve the work performance of employees.